2020
DOI: 10.3390/jcm9030883
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Retinal Microvasculature Measured Using Optical Coherence Tomography Angiography According to Age

Abstract: In this cross-sectional study, we examined age-related changes in the retinal vessels of 100 healthy participants, aged from 5 to 80 years, and divided into four groups (G1, under 20 years of age; G2, from 20 to 39 years of age; G3, from 40 to 59 years of age; G4, age 60 years or older). All subjects underwent swept-source optical coherence tomography (SS-OCT) and OCT angiography (OCTA). The vascular density (VD) of the superficial (SCP) and deep capillary plexus (DCP), and choriocapillaris (CCP) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
1
17
1
1
Order By: Relevance
“…Previous studies identified age-related changes in retinal vascular density, with a reduction in vascular density reported in older populations across the two studies [39,40]. We found no significant changes in vascular density to be associated with either age or gender; however, the specific parameters of our experimental design precluded the assessment of an equivalent age-range to these studies, which may explain why any effect of age did not reach significance in the current study.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies identified age-related changes in retinal vascular density, with a reduction in vascular density reported in older populations across the two studies [39,40]. We found no significant changes in vascular density to be associated with either age or gender; however, the specific parameters of our experimental design precluded the assessment of an equivalent age-range to these studies, which may explain why any effect of age did not reach significance in the current study.…”
Section: Discussioncontrasting
confidence: 69%
“…OCTA was used to explore pathophysiologic features of certain diseases [12][13][14][15][16]. Most previous studies using OCTA, however, mainly have evaluated normal adult patients [1,4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential utility, vascular density (VD) data in normal children's eyes is limited, and clinical applications in children are also sparse [ 1 , 6 , 7 ]. There are few studies that have attempted to present normative data about children [ 6 , 8 , 9 ]. Thus, the objective of this research was to report macular microvascular measures in healthy Iranian pediatric individuals using OCTA analysis, as well as to assess the factors that may affect this quantitative data.…”
Section: Introductionmentioning
confidence: 99%
“…OCTA was used to explore pathophysiologic features of certain diseases [ [12][13][14][15][16]]. Most previous studies using OCTA, however, mainly have evaluated normal adult patients [1,4,5,9]. FAZ was reported to be 0.26-0.47 mm using different kinds of OCTA machines at 3 × 3-mm enface AngioScans in the kids between mean age of 8-12 years in different capillary layers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential utility, vascular density (VD) data in normal children's eyes is limited, and clinical applications in children are also sparse [1,6,7]. Few research attempted to present children's normative data [6,8,9]. Thus, the objective of this research was to report macular microvascular measures in healthy Iranian pediatric individuals using OCTA analysis, as well as to assess the factors that may affect this quantitative data.…”
Section: Introductionmentioning
confidence: 99%